Clostridioides difficile-mesocolonic oedema in neonatal suckling piglets develops regardless of the fibre composition in sow’s diets - Łukasz Grześkowiak; Eva-Maria Saliu; Anna Grete Wessels; Beatriz Martínez-Vallespín; Klaus Männer; José Joaquín Cerón; Wilfried Vahjen; Jürgen Zentek (Animal, 2023)
Maternal dietary factors have been reported to influence Clostridioides difficile colonisation in the offspring. Twenty suckling piglets from sows fed diets supplemented with high-fermentable sugar beet pulp (SBP) or low-fermentable lignocellulose (LNC) fibres during gestation and lactation were dissected in the first week after birth. Postmortem analysis included clinical mesocolon and faecal scoring, concentration of C. difficile and respective toxins in colon digesta and faeces, immunoglobulins in serum and inflammatory markers in serum and colon tissues. Sow colostrum was assessed for nutrients, immunoglobulins and biogenic amines. Toxin-neutralising IgG antibodies were measured in colostrum and serum of the sows, and in colon digesta and serum of the piglets. Mesocolonic oedema of different severity was present in most of the piglets from both sows’ feeding groups. Concentrations of C. difficile, toxins and calprotectin in colon digesta and faecal contents did not differ between the study piglets. Calprotectin correlated positively with mesocolon score (rho = 413, P = 0.07). Piglets from sows fed LNC vs SBP tended to have higher IgA (P = 0.089), IgG (P = 0.053), total Ig (P = 0.053), albumin (P = 0.075) and total protein content (P = 0.007) in serum. Colon tissues of piglets from the SFB vs LNC had upregulated expression of ZO-1 (P = 0.021), PCNA (P = 0.015) and TGF-β (P = 0.014). Titers of anti-toxin-IgG-antibodies in serum and colostrum and in piglet colon digesta and serum did not differ between sows from both dietary groups, but they all showed strong positive correlations. In conclusion, dietary sugar beet pulp or lignocellulose fed to sows did not influence the concentrations of C. difficile and toxins titers in colon digesta and faeces of neonatal piglets.